Criminal Law Enforcement Against Perpetrators of the Crime of Flying Hot Air Balloons (Study of Decision Number 114.Pid.B/2022/PN Mjy) - Mona Tarisa; Sugih Ayu Pratitis (Civiliza Publishing, 2026)
Hot air balloon flights are considered as dangerous for aviation safety because they can interfere with air traffic and endangered aircraft, particularly when balloon materials risk being drawn into aircraft propellers. The Ministry of Transportation states that unauthorized hot air balloon flights may be subject to Article 411 of Law Number 1 of 2009 on Aviation, which provides for a maximum imprisonment of two years and a fine of up to IDR 500,000,000. This study examines the hot air balloon case decided in Decision Number 114/Pid.B/2022/PN Mjy, involving several defendants. The main legal issue concerns the judges' considerations in applying Article 411, given that the provision does not explicitly mention hot air balloons in its elements. Using normative juridical research based on secondary data and qualitative analysis, the study finds that the judges imposed criminal sanctions on the grounds that the defendants' actions violated Article 411 of the Aviation Law and Ministry of Transportation Regulation Number 40 of 2018. The defendants were sentenced to one month's imprisonment and a fine of IDR 1,000,000 each. However, ideally, criminal sanctions should not have been imposed due to the absence of explicit regulation of hot air balloons in Article 411